1307 Linking Pre-ST Trainees into The Surgical Profession - An Example from OMFS Of A Structured Introduction to The Speciality. (12th October 2021) - McLean, A; Rapaport, B
Abstract: Introduction: Inspiration and support are two of the key principles that enthuse junior trainees to pursue a career in surgery. Exposure to Oral and Maxillofacial Surgery (OMFS) is minimal at undergraduate level and can present a challenge for those postgraduate individuals who wish to gain more experience before applying to further training. This has prompted the formation of a support programme comprised of two stages: Taste of OMFS and Mentoring and Support Programme (MSP). Method: Feedback was captured from OMFS junior trainees and educational supervisors on the existing junior trainee programme. It was concluded that a new programme was required to create a more structured system to help support trainees achieve their goals within OMFS. Taste in OMFS aims to provoke intrigue in the specialty. Individuals who are inspired to experience more can advance on to the MSP which consists of checklists, carefully designed to help the trainee obtain adequate exposure and achieve the recommended requirements for second-degree and specialty training applications. Results: The new programme was trialed by existing junior trainee programme members over a six-month period. The results were encouraging with positive feedback on the structure of both sections. This, in combination with ideas generated from a focus group has helped create the final version, now published and accessible on the British Association of Oral and Maxillofacial Surgeons website. Conclusions: We hope to raise awareness of this dynamic programme which can be tailored to each individual, in the hope that more junior trainees pursue a career within OMFS.